2014
DOI: 10.2478/amm-2014-0204
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Heat Treatment Conditions on Microstructure and Mechanical Properties of Austempered Ductile Iron After Dynamic Deformation Test

Abstract: In this article, an attempt was made to determine the effect of dynamic load on the austempered ductile iron resistance obtained under different conditions of heat treatment. Tests were carried out on six types of cylindrical ductile iron samples austempered at 320, 370 and 400• C for 30 and 180 minutes. For each type of material, two samples were collected. As a next step in the investigations, the samples were subjected to a Taylor impact test. The samples after striking a non-deformable, rigid target were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…18) deformed as a result of dynamic strain after the Taylor's test lies flat to the surface [37]. Chinella et al [38] found a significant deformation of graphite nodules after a ballistic test.…”
Section: Discussionmentioning
confidence: 99%
“…18) deformed as a result of dynamic strain after the Taylor's test lies flat to the surface [37]. Chinella et al [38] found a significant deformation of graphite nodules after a ballistic test.…”
Section: Discussionmentioning
confidence: 99%
“…The investigated samples were machined from the cast blocks into cylindrical shape with 8 mm diameter and 28 mm length. According to Taylor assumptions which are described in detailed in different references [5][6], the dynamic yield strength could be calculated using the following equation (Eq.1):…”
Section: Taylor Impact Testmentioning
confidence: 99%
“…Yamamoto et al [9] investigated the strain rate effects at different temperatures of as-cast and ferritic annealed DCI using Charpy impact test. Myszka et al [10] analyzed several grades of ADI, austempered at different temperatures, using Taylor's cylinder impact test, with the attempt to determine the effect of dynamic load on the strain driven transformation of matrix phases. No information is available, to the best authors' knowledge, about the mechanism by which the strain rate affects the ADIs ductility.…”
Section: Introductionmentioning
confidence: 99%